EVALUASI PROGRAM KELAS AKSELERASI DI SD AL-AZHAR SYIFA BUDI KEMANG, JAKARTA SELATAN - elida fitri, sani; Setiadi, Hari; Ernawati, Ernawati (Jurnal Penelitian dan Penilaian Pendidikan, 2024)
Accelerated class is a class intended for students whose learning isaccelerated with a level of understanding of the material so that they can take theirstudy time faster than the time specified in the regular class. The aim is to obtain in-depth information about the accelerated class program covering matters that areimportant aspects of the evaluation with the CIPP model to be further processed andproduce a positive recommendation. This evaluation uses a qualitative approach andcollects data using observation, interview and document study methods. Interviewdata were obtained from residents of SD Al-Azhar Syifa Budi Jakarta, including;Principal, Vice Principal, Teacher. And for document data in the form of Vision andMission documents, School Profiles, and National Exam scores for accelerated classstudents. The evaluation results show that on; context component; Vision and Missionprovide a place for special intelligent students to take part in educational programs according to their intelligence potential. input components; 1) There is a specialacceptance of accelerated students, 2) There is an allocation of the acceleratedprogram budget 3) In general, the competency of accelerated teachers meets inputindicator standards, 4) The curriculum and accelerated program are implemented asone unit. process component; 1) The learning activities of the accelerated classprogram are faster than regular classes, 2) The implementation of supervisionactivities for the accelerated class program is not effective. product components; 1)The National Exam scores of accelerated class program students have an averagescore of very good, 2) The output/quality of accelerated graduates is on averageaccepted at well-known junior high schools/equivalents. After considering a numberof indicators in the evaluation, as well as based on the four components in theevaluation with the CIPP model (Context, Input, Process, Product) it can beconcluded that the implementation of the accelerated class program is going very welleven though at the point of implementing the acceleration class program.